English Students’ Perception Towards Online Learning at State University of Makassar - Rosita, Siti; Noni, Nurdin; Samtidar, Samtidar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This research aims to find out the perceptions of English education study program students towards online learning at State University of Makassar. In this research, the researcher used a mixed-method research design. The population of this research is 7th semester students of English education at State University of Makassar. The number of populations is 68 students. The researcher used random sampling techniques in determining the sample. The researcher used questioner and interview, consists of 15 questioner and 5 interview questions. The result of this research shows that students have a positive perception of online learning, it was proven by the result of the students’ rating mean which was 57.54. The perceptions of learners of online learning, which makes it simpler to receive learning materials because it can be accessible anywhere and anytime, show that it is properly effective, can help students to receive learning and students are increasing in seeking information from various sources.